THE ANALYSIS OF MORAL MESSAGE CONTAINED ON “LITTLE WOMEN” NOVEL BY LOUISA ALCOTT - Nawawi, Imam (IdeBahasa, 2023)
This study examines a moral lesson found in the novel "Little Women" by American white writer Louisa May Alcott The life lessons depicted in the novel of little women is one in which people interact with each other through actions and behaviors. Through these morals, it also aims to study the roots of these morals as part of social values as well as the society of mid-19th century mirrored in the novel. According to Nurgiyantoro (1995), moral values in literature encompass the individual's relationship with humanity, God, social life, and the interconnectedness of life with nature. In the novel, characters face emotional challenges, prioritize financial gain through writing, believe money brings happiness at home, display stubbornness, value personal freedom, speak harshly, and harm their siblings' belongings. They also express their faith through prayers, praising God, and referencing religious figures. The main character maintains confidence in their wishes and shows gratitude to the divine. The characters teach valuable lessons about self-love, courage, overcoming inferiority, building confidence, and independent problem-solving, treating these experiences as life lessons. The novel emphasizes kindness towards those in need, encouraging readers to offer assistance and share with others. Overall, "Little Women" reminds us to slow down, appreciate what we have, and stand up for ourselves.. This study adopts a descriptive qualitative approach to examine the moral components of the novel. Data collection involves reading, note-taking, and analyzing relevant quotes, remarks, and activities. All data utilized in the study are written texts, with the novel serving as the primary source. Supplementary materials such as books, journals, and online sources are considered secondary data. The research process encompasses data collection, selection, and analysis within the context of library research.